PENGARUH BAURAN PROMOSI TERHADAP VOLUME PENJUALAN PADA PABRIK MESIN INDUSTRI KECAMATAN GEGER KABUPATEN MADIUN - Agus Prasetyo (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
This study aims to determine how the promotion mix at the Plant Engineering Industrial District Geger Madiun, to determine the volume of sales to the Plant Engineering Industrial District Geger Madiun District, as well as to determine whether or not Influence Between the promotional mix Against the volume of sales to the Plant Engineering Industrial District Geger District Madiun. The samples in this research is to use a purposive sampling (samples intended) is the result of five years of production at the Plant Engineering Industrial District Geger Madiun. Collecting data using the method of documentation, interviews and observasi.Dalam analyze data using statistical methods Product Moment to test the hypotheses put forward in the study tested the hypothesis using the test ..TO r, F test and t test. The results showed that the promotion mix has an influence on the volume of sales to the Plant Engineering Industrial District Geger Madiun. It is obtained from the correlation test showed that the value rhitung is 0.8476 while rtabel 0.648. In addition Sighit value is 0,000 while Sigprob 0.05. This means that the value rhitung ≥ rtabel (0.8476 ≥ 0.648) or ≤ Sighit Sigprob (0,000 ≤ 0.05). On the basis of the correlation test, we can conclude H0 is rejected, it means that there is a connection with the promotion mix sales volumes in the "Plant Engineering Industry" Kecamatan Geger Madiun.